Surgically treated pediatric tongue masses: A 20 Year review. (March 2023) - Leonard, James A.; Blumenthal, Daniel L.; Bauman, Nancy M.; Rana, M. Sohel; Peña, Maria T.; Espinel, Alexandra G.
Abstract: Objective: Pediatric tongue lesions represent a rare, diverse group of pathologies related to congenital malformations, inflammatory changes, and neoplastic masses. We present the largest-to-date series of pediatric tongue lesions managed surgically. Setting: Charts of all pediatric patients with a tongue lesion surgically treated at a regional children's hospital from February 1st, 1997 to August 30th, 2019 were reviewed. Methods: After obtaining institutional review board approval, a retrospective review was completed of all pediatric patients with a tongue lesion surgically treated at a regional children's hospital from February 1st, 1997 through August 30th, 2019. Charts were evaluated for patient demographics as well as symptoms at presentation, surgical details, pathologic evaluation of the lesion, and rates of recurrence. Categorical variables were compared between various groups using Chi-square and/or Fisher's exact tests. Univariate and multivariable logistic regression analysis was performed unadjusted and adjusted to further explore these relationships. Results: 159 patients were included in the study with ages distributed relatively even across infants (27.7%), children 1–5 years (27.7%), 6–10 years (23.3%), and greater than 10 years of age (21.4%). Patient/family reported race/ethnic background was most commonly Caucasian (34.8%) or Hispanic/Latino/Spanish Origin (34.0%) followed by Black or African American (21.3%). The most commonly reported symptoms were pain (23.3%), difficulty with oral intake (12.6%), bleeding (11.3%), and respiratory distress (11%). Patients with lesions of the base of tongue were significantly more likely to present with respiratory distress or difficulty with oral intake (p < 0.001). The likelihood of recurrence was observed to be higher with lesions managed in infancy (OR 3.85, CI 1.47–10.0, p = 0.005), those greater than 2 cm (OR 3.45, CI 1.34–8.71, p = 0.009), or with laser (OR 4.52, CI 1.25–15.00), p = 0.015). Conclusion: Pediatric patients with tongue lesions may present with a wide array of symptoms. Base of tongue lesions should be managed carefully as they are most likely to create barriers to the airway and oral intake. Larger lesions and those managed in infancy are at increased risk for recurrence.